ChemESI (Chemical Environmental Sustainability Index)—A KPI (Key Performance Indicator) for Standardizing Environmental Metrics for Chemical Sustainability - Plugge, Hans (Frontiers in Sustainability, 2022)
As part of the ESG (Environmental, Social and Governance) dynamics, chemical environmental sustainability i.e., the impact from chemicals and how to measure it across hundreds of products, is a daunting, but necessary task. Although methods are available to measure the effects and impacts of a single chemical, most enterprises do not focus on a single chemical, let alone produce “pure” chemicals for sale. Nearly all chemicals in commerce are chemical products i.e. mixtures, while assessment methods for mixtures are few and far between. What is needed is a metric that tracks the potential risk of an enterprise’s total product inventory while monitoring its improvements as it greens in coming years. The Chemical Environmental Sustainability Index (ChemESI) metric measures both risk (as the product of exposure and hazard) and hazard across numerous chemicals as a single metric/KPI. The ChemESI’s for chemicals, products and facilities are expressed such that they can be summed across facilities to wrap up into a single corporate ChemESI KPI for either hazard or risk. But what about growth – if growth occurs using greener chemical inventory, a company can both grow and improves its ChemESI KPI. Given the lead-time for developing more, true green alternatives to existing chemicals, intermediate substitution of less hazardous “analogues” may drive initial ChemESI reduction. To achieve a representative risk estimate, a primary data need is chemical characterization data for products. SDS’s (Safety Data Sheets) unfortunately make poor substitutes for true constituent analyses. A definite need exists for better, more detailed chemical characterization data for both mixtures and individual chemicals, as the latter most often are not 100 % “pure”. However, these SDS’s are available universally, across the globe, and provide GHS (UN Globally Harmonized System) classifications for single endpoint chemical hazard assessment. GHS classifications are near universal and here used to derive chemical hazard scores over multiple endpoints for each chemical. A ChemESI Risk metric can be derived by multiplying the hazard score by the exposure, here using inventory as a surrogate. The ChemESI Hazard metric is then derived as an inventory weighted hazard score.